RF magnetron-sputtered coatings deposited from biphasic calcium phosphate targets for biomedical implant applications; Bioactive Materials; Vol. 2, iss. 3 - Prosolov K. A. Konstantin Alexandrovich; Popova K. S. Kseniya Sergeevna; Belyavskaya O. A. Olga Andreevna; Rau Ju. V. Julietta; Gross K. A. Karlis Agris; Ubelis A. P. Arnolds; Sharkeev Yu. P. Yury Petrovich (2017, 2017)
Title screen